JURIDICAL REVIEW OF MARRIAGE ANNULMENT DUE TO IDENTITY FORGERY ACCORDING TO ARTICLE 27 OF LAW NUMBER 1 OF 1974 CONCERNING MARRIAGE - S.A, Rd.N.Sayyidatussa'adah; Abas, Muhamad; Dewi, Sartika (Justisi: Jurnal Ilmu Hukum, 2024)
Marriage is living together of a man and a woman who meet certain conditions, a marriage can be annulled due to a violation of the prohibition, this shows the damage or cancellation of something that is prohibited because it does not meet the requirements and harmony according to the law. The issues raised in this study are how marriages are annulled as a result of identity falsification according to law number 1 of 1974 which has been amended by law number 16 of 2019 about marriage and how are the judge's considerations regarding word number 1767/Pdt.G/2017 /PA. Krw. The purpose of this research is to find out the cancellation of marriage due to falsification of identity according to law number 1 of 1974 which has been amended by law number 16 of 2019 about marriage and to find out the judge's considerations regarding word number 1767/Pdt.G/2017/PA .Krw. In this study the authors used a type of qualitative research using the Normative Juridical approach, the purpose of which was to analyze the problem by examining legal materials. The result of the author's research are in the decision 1767/Pdt.G/2017/PA.Krw. The existence of an annulment of marriage related to carrying out a marriage with identity falsification carried out by the husband and the implementation of the marriage has violated Article 27 paragraph (2) of Law Number 1 1974 which has been amended by law number 16 of 2019 about Marriage. The cancellation of the marriage itself is when a marriage that has taken place can be canceled if one of the parties does not meet the conditions set for the marriage. as a result, the marriage that was carried out immediately broke up and was considered as if it had never existed.